Competitividade empresarial na indústria de colheitadeiras: o caso John Deere - Veiga, Cristiano Henrique Antonelli da (2003)
This dissertation aims the study of the practical concepts and methods used to measure the factors of industry competitiveness and how they influence the results in a particular company. It was emphasized the main authors that wrote about the subject, as well as it was performed a critical approach on it and it was investigated the factors of competitiveness in that particular company. It was developed a methodology based on Porter (1986), Ferraz et al. (1995) and Ghemawat (2000) models on the attempt of identifying which are the factors and how they interfere on market competitiveness in an industry that manufactories combines for the Brazilian market. This study is made up of seven chapters that define the introduction, a bibliographic revision about the concept of competitiveness, the factors of competitiveness, the methodological uses, Brazilian agribusiness and the combines market panorama, the results of the research and the conclusion.